Long photoperiod restores the 24-h rhythm of sleep and EEG slow-wave activity in the Djungarian hamster (Phodopus sungorus). - Deboer, T; Vyazovskiy, V; Tobler, I (2000)
Photoperiod influences the distribution of sleep and waking and electroencephalogram (EEG) power density in the Djungarian hamster. In an experimental procedure combining short photoperiod (SP) and low ambient temperature, the light-dark difference in the amount of sleep was decreased, and the changes in slow-wave activity (SWA) (mean EEG power density between 0.75 and 4.0 Hz) in nonrapid eye movement (NREM) sleep within 24 h were abolished. These findings, obtained in three different groups of animals, suggested that at the lower ambient temperature, the influence of the circadian clock on sleep-wake behavior was diminished. However, it remained unclear whether the changes were due to the photoperiod, ambient temperature, or both. Here, the authors show that EEG and electromyogram recordings in a single group of animals sequentially adapted to a short and long photoperiod (LP) at low ambient temperature (approximately 15 degrees C) confirm that EEG power is reduced in SP. Moreover, the nocturnal sleep-wake behavior and the changes in SWA in NREM sleep over 24 h were restored by returning the animals to LP and retaining ambient temperature at 15 degrees C. Therefore, the effects cannot be attributed to ambient temperature alone but are due to a combined effect of temperature and photoperiod. When the Djungarian hamster adapts to winter conditions, it appears to uncouple sleep regulation from the circadian clock.